Wege zu einer nachhaltigen Abfallwirtschaft. - (:unkn) unknown (My University, 2010)
Die Problemfelder der Abfallwirtschaft werden detailliert beschrieben und Lösungswege werden aufgezeichnet. Dabei wird ein Schwerpunkt auf Hausmüll, Sperrmüll und hausmüllähnlichen Gewerbeabfällen gesetzt. Die Kernaussagen zur Abfallvermeidung, zur getrennten Erfassung, zur Verwertung und zur Abfallverbrennung gelten aber für alle Sektoren der Wirtschaft, also auch für die Industrie.

While the total amount of waste has stayed almost the same in Germany over the past years, the volume of separately collected and recycled waste has increased. The amount of residual waste has decreased accordingly. Hence, in spite of some success regarding waste recycling, not enough has been achieved in waste prevention. This is apparent with respect to the development of quotas for the refillable beverage packaging, a prime example for reuse. While the quotas for the packaging of beer have remained at a high level, they have been declining considerably for other beverages. The introduction of a refund on non-reusable packaging could not reverse this trend. In order to reduce the total amount of waste in Germany, efforts have to be intensified towards implementation of waste prevention measures both in private households and in trade and industry.
Keywords: Siedlungsabfall; Abfallwirtschaft; Abfallmenge; Abfallart; Abfallbehandlung; Abfallverwertung; Abfalltransport; Abfallvermeidung; Handlungsempfehlung